Researching China in Southeast Asia, 1st edition - Chow-Bing, Ngeow (Routledge, 2020)
This book maps out the state of China Studies in seven Southeast Asian countries from different perspectives. It looks at the history, current status, and characteristics of the study of China in Indonesia, the Philippines, Thailand, Vietnam, Malaysia, Singapore, and Myanmar, and what factors shaped the development and prospects of Sinology and Chinese Studies in these countries.